HUBUNGAN ANTARA KECERDASAN LOGIS MATEMATIS DENGAN KEMAMPUAN COMPUTATIONAL THINKING SISWA SMP - Dewi, Kadek Cintya Purnama Dewi; Pujawan, I Gusti Ngurah; Hartawan, I Gusti Nyoman Yudi; Widnyana, Gede Supanca (De Fermat : Jurnal Pendidikan Matematika, 2026)
The development of the 21st century requires students to possess higher-order thinking skills, one of which is computational thinking, which plays a crucial role in systematic problem-solving. However, students’ computational thinking skills have not yet reached their optimal potential, highlighting the need to investigate factors that influence them. Logical-mathematical intelligence is considered one of these factors. This study aims to identify and characterize the correlation between logical-mathematical intelligence and computational thinking skills among junior high school students. The sample consisted of 29 ninth-grade students from SMP Satu Atap Negeri 3 Banjar, located in Buleleng, Bali. The research instruments included validated multiple-choice tests to measure logical-mathematical intelligence and essay tests to assess computational thinking skills. Data were analyzed using normality tests, linearity tests, and the Pearson Product-Moment correlation test. The prerequisite tests indicated that the data were normally distributed and exhibited a linear relationship. The results of hypothesis testing revealed a significant positive correlation between logical-mathematical intelligence and computational thinking skills, with a correlation coefficient of 0.781, which is categorized as strong. This finding indicates that students’ computational thinking skills are directly proportional to their level of logical-mathematical intelligence.